The Comparison of the English Versions of Poem Lu Zhai: Taking G.W. Robinson and Xu Yuanchong’s Versions as Examples - Zhao, Xuefei (Pacific International Journal, 2024)
Chinese classical poetry, as a treasure of Chinese culture, has always attracted numerous translators. Translating classical poetry not only requires accurately conveying the artistic conception and expression of the original work, but also requires flexible application of translation techniques to adapt to different language and cultural backgrounds. Poetry translation is a difficult point in the translation of literary works, and poetry is known as “literature in literature”. Its form is brief but its meaning is profound, “words are here and meaning is there, words are full and meaning is infinite”. This article will take the classic Chinese classical poem “Lu Zhai"”as an example, and use the method of literature review to collect and analyze G W. Translated versions by two translators, G.W. Robinson and Xu Yuanchong. Firstly, a comprehensive reading and understanding of the two versions were conducted. Secondly, by comparing the translation styles of the two versions, we compared rhyme, image, sentence as well as arrangement. Through these comparisons, the article draws conclusions about the different stylistic characteristics of the two translators. This study is of great significance in revealing translators’ understanding and expression of classical poetry.